2004
DOI: 10.1007/s00284-003-4192-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of a Burkholderia pseudomallei Collagenase in Escherichia coli

Abstract: Extracellular protein profiles were compared for broth-grown cultures of Burkholderia pseudomallei and its avirulent close relative Burkholderia thailandensis. A number of protein bands were present in the B. pseudomallei profile but absent or less abundant in the B. thailandensis profile. Four such prominent secreted proteins were identified by using N-terminal sequencing coupled to searches of the B. pseudomallei genome sequence database. The genes for two proteins with similarity to carbohydrate-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Three of these proteins, BURPS668_2041, BURPS668_A0759, and BURPS668_1946, were identified in this study as members of the T2SS secretome ( Table 2). The last protein, BURPS668_ A1216, was a protein with homology to known bacterial collagenases (47). We found two putative collagenases, including BURPS668_A1216, that were present in roughly equal amounts in the rich-medium supernatants of MSHR668 and 668 ⌬gspD, suggesting that they are secreted in a T2SS-independent manner (Table 3).…”
Section: Construction and Initial Characterization Of B Pseudomalleimentioning
confidence: 81%
See 1 more Smart Citation
“…Three of these proteins, BURPS668_2041, BURPS668_A0759, and BURPS668_1946, were identified in this study as members of the T2SS secretome ( Table 2). The last protein, BURPS668_ A1216, was a protein with homology to known bacterial collagenases (47). We found two putative collagenases, including BURPS668_A1216, that were present in roughly equal amounts in the rich-medium supernatants of MSHR668 and 668 ⌬gspD, suggesting that they are secreted in a T2SS-independent manner (Table 3).…”
Section: Construction and Initial Characterization Of B Pseudomalleimentioning
confidence: 81%
“…In 2004, Rainbow et al (47) performed N-terminal sequencing on four proteins that were present in the supernatant of pathogenic B. pseudomallei but absent in the supernatant of nonpathogenic B. thailandensis. Three of these proteins, BURPS668_2041, BURPS668_A0759, and BURPS668_1946, were identified in this study as members of the T2SS secretome ( Table 2).…”
Section: Construction and Initial Characterization Of B Pseudomalleimentioning
confidence: 99%
“…Burkholderiaceae is a family of proteobacteria which contains many human and animal pathogens (diCenzo et al 2019), plant and insect symbionts (Gyaneshwar et al 2011;Takeshita and Kikuchi 2017), and can be found in soil, water, and polluted environments (Coenye and Vandamme 2003;Estrada-de los Santos et al 2016). They also include some collagenase-producing bacteria, such as Burkholderia pseudomallei (Uni-ProtKB -A3P3M6; Rainbow et al 2004), which is the causative agent of melioidosis in humans (Holden et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderiaceae is a family of proteobacteria which contains many human and animal pathogens (diCenzo et al 2019), plant and insect symbionts (Gyaneshwar et al 2011; Takeshita and Kikuchi 2017), and can be found in soil, water, and polluted environments (Coenye and Vandamme 2003; Estrada-de los Santos et al 2016). They also include some collagenase-producing bacteria, such as Burkholderia pseudomallei (UniProtKB – A3P3M6; Rainbow et al 2004), which is the causative agent of melioidosis in humans (Holden et al 2004).…”
Section: Discussionmentioning
confidence: 99%